The efficacy of pursed lips breathing on enhancing thoracic expansion in active smokers: A quasi-experimental study in Salimpaung District, Indonesia - Olyverdi, Reza; Legumes (Utan Kayu Publishing, 2025)
Smoking impairs lung function as hemoglobin binds more easily to carbon dioxide than oxygen, weakening respiratory muscles and reducing thoracic expansion. This condition increases the risk of shortness of breath and respiratory complications. Pursed Lips Breathing (PLB) is a breathing technique that improves alveolar ventilation and strengthens respiratory muscles, ultimately enhancing thoracic expansion. This quasi-experimental study aimed to determine the effect of PLB on thoracic expansion in active smokers. The study was conducted from March 13 to March 26, 2023, involving 15 active male smokers aged 30–40 years in Salimpaung District, Tanah Datar Regency. Thoracic expansion was measured at three anatomical points: axilla, costa 4, and xyphoid process using the midline technique. The findings showed significant increases in thoracic expansion at all measurement points. The mean expansion at the axilla improved from 1.07 cm to 2.73 cm (p = 0.000), at costa 4 from 2.20 cm to 5.33 cm (p = 0.001), and at the xyphoid process from 4.73 cm to 7.27 cm (p = 0.001). These results confirm the positive effect of PLB on thoracic expansion in active smokers. In conclusion, PLB is an effective intervention for enhancing thoracic expansion and improving respiratory function in active smokers. It can be a practical and accessible method for respiratory rehabilitation, particularly for populations with limited access to medical facilities. The adoption of PLB may help reduce respiratory complications and improve overall lung capacity in smokers.